Why Studies in the Effect of Positive Psychological Interventions Should Use Life-Satisfaction as an Outcome - Veenhoven, Ruut (Frontiers in Psychology, 2021)
The effect of positive psychological interventions (PPIs) is mostly assessed using self-report measures of positive mental health. These measures are problematic because 1) the content addressed is often not clear, 2) different scales are used to assess different notions of positive mental health, which impedes comparability, 3) the concept of positive mental health involves objective capabilities which are not well measurable using subjective self-estimates, and 4) the concept behind the measures denote presumed chances for adaptation to life rather than adaptation as such. Therefore. we should also measure the effect of PPIs using life-satisfaction, which is a) a clear-cut concept and as such tells us what an intervention brings about, b) is well measurable using self-reports, since it is a subjective concept, c) it allows better comparability across studies and d), it indicates actual adaptation to life instead of presumed strengthening of chances for adaptation.